Socioeconomic Status, Smoking, Alcohol use, Physical Activity, and Dietary Behavior as Determinants of Obesity and Body Mass Index in the United States: Findings from the National Health Interview Survey - Raees A. Shaikh, MD, MPH; Mohammad Siahpush, PhD; Gopal K. Singh, PhD; Melissa Tibbits, PhD (Global Health and Education Projects, Inc., 2015)
Objectives: The aim of this research was to study the socio-demographic and behavioral determinants of obesity and Body Mass Index (BMI) in the United States, using a nationally representative sample. Methods: We used data from the 2010 US National Health Interview Survey. Analyses were limited to adults 18 years and older (N=23,434). Multivariate regression analyses were conducted to estimate the associations between covariates and obesity and BMI. Results: Overall, 28.1% in the sample were obese and the mean BMI was 27.6 kg/m2 . In adjusted models, we found that older age, non-Hispanic Black race, lower education and income levels, Midwestern and Southern region of residence, former smoking, infrequent alcohol use, physical inactivity, consumption of less fruits, vegetables, brown rice and more cheese, fried potato and meat, were associated with obesity. These factors were also associated with higher BMI, along with male gender and higher consumption of meat, fried potatoes and cheese. Conclusions and Global Health Implications: The association of many of the socio-demographic and behavioral factors with obesity and higher BMI found in our study was consistent with previous findings. Persistence of such associations suggest a need for better understanding of the underlying mechanism as well as for evaluation of the current programs and policies targeted at reducing the obesity burden in the United States. In view of the rising global obesity epidemic, especially in the low- and middle-income countries, our findings could help guide development of effective health and social policies and programs aimed at reducing the obesity burden in other parts of the world. Key words: Obesity • Body Mass Index • Socioeconomic status • Physical activity • Diet • Smoking • Alcohol use • Disparity • United States • National Health Interview Survey Copyright © 2015 Shaikh et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.